Analysis of the contribution of FTO, NPC1, ENPP1, NEGR1, GNPDA2 and MC4R genes to obesity in Mexican children - Mejía-Benítez Aurora; Klünder-Klünder Miguel; Yengo Loic; Meyre David; Aradillas Celia; Cruz Esperanza; Pérez-Luque Elva; Malacara Juan Manuel; Garay Maria Eugenia; Peralta-Romero Jesús; Flores-Huerta Samuel; García-Mena Jaime; et al. (BMC, 2013)
Abstract Background Recent genome wide association studies (GWAS) and previous positional linkage studies have identified more than 50 single nucleotide polymorphisms (SNPs) associated with obesity, mostly in Europeans. We aimed to assess the contribution of some of these SNPs to obesity risk and to the variation of related metabolic traits, in Mexican children. Methods The association of six European obesity-related SNPs in or near FTO, NPC1, ENPP1, NEGR1, GNPDA2 and MC4R genes with risk of obesity was tested in 1,463 school-aged Mexican children (Ncases = 514; Ncontrols = 949). We also assessed effects of these SNPs on the variation of body mass index (BMI), fasting serum insulin levels, fasting plasma glucose levels, total cholesterol and triglyceride levels, in a subset of 1,171 nonobese Mexican children. Results We found a significant effect of GNPDA2 rs10938397 on risk of obesity (odds ratio [OR] = 1.30; P = 1.34 × 10-3). Furthermore, we found nominal associations between obesity risk or BMI variation and the following SNPs: ENPP1 rs7754561, MC4R rs17782313 and NEGR1 rs2815752. Importantly, the at-risk alleles of both MC4R rs17782313 and NPC1 rs1805081 showed significant effect on increased fasting glucose levels (β = 0.36 mmol/L; P = 1.47 × 10-3) and decreased fasting serum insulin levels (β = −0.10 μU/mL; P = 1.21 × 10-3), respectively. Conclusion Our present results suggest that some obesity-associated SNPs previously reported in Europeans also associate with risk of obesity, or metabolic quantitative traits, in Mexican children. Importantly, we found new associations between MC4R and fasting glucose levels, and between NPC1 and fasting insulin levels.